(untitled) (Journal of Information Technology and Digital World, 2020)
In this paper, a temperature monitoring system for glass manufacturing process is proposed by using Fibre Bragg Grating (FBG) approach. This system can be done by using OptiSystem simulation. FBG was used as it allows a reflects a wavelength of light that shifts according to variations in temperature. Generally, FBG sensors can be easily installed, it has higher accuracy, longer stability, small in size, immunity to electromagnetic interference (EMI) and the ability to measure ultra-high and speed events. The results indicated that wavelength shifting is depended on thermal expansion coefficient and thermo-optic coefficient of materials, from simulation results it was seen that, Tungsten DiSulfide(WS2) has a better sensitivity than Silica, Poly Methyl Methacrylate(PMMA) and Lead Sulfide(PbS).